Learning Effectiveness of Semi Practice Course in Online Learning - Tri Sudarwanto; Eka Hendi Andriansyah; Raya Sulistyowati; Septyan Budy Cahya; Veni Rafida (Institut Agama Islam Negeri Imam Bonjol Padang, 2023)
The COVID-19 pandemic has resulted learning activities in universities and schools temporarily stopping face-to-face learning, especially in Indonesia. Instead, learning is conducted remotely online. The application of online learning requires the readiness of several parties, from the provision of infrastructure to the students' side. The problem of cost, the readiness of educators and students in using technology is still the reason online learning can be carried out after the Covid19 pandemic in an effort to integrate technology in the world of education. How do we optimize the quality of Education through online learning. The research is aimed at knowing the effectiveness of online learning in learning media courses in the midst of a pandemic. It also includes planning, implementing, evaluating, as well as obstacles and how to overcome them. This research was conducted with a qualitative descriptive method. This study will describe the problems and solutions that occur in online learning so that the effectiveness of its implementation can be determined and recommendations for the feasibility of online learning can be determined in the future. Data collection techniques were carried out by documentary studies, observations, and interviews. The results showed that learning from semi-practical courses was running effectively. Various problems that become the issue of the weakness of online learning are solved by government policies, campus facilities and services that are able to support the achievement of learning objectives even in semi-practical courses.